Integrated multi-omics analyses combined with western blotting discovered that cis-TSG alleviated liver injury via modulating lipid metabolism - Teka, Tekleab; Wu, Jiang; Oduro, Patrick Kwabena; Li, Ze; Wang, Chenxi; Chen, Hao; Zhang, Lin; Wang, Haitao; Wang, Liming; Han, Lifeng (Frontiers in Pharmacology, 2024)
Background:Polygonum multiflorum shows dual hepatoprotective and hepatotoxic effects. The bioactive components responsible for these effects are unknown. This study investigates whether cis-2,3,5,4'-tetrahydroxystilbene-2-O-β-D-glucoside (cis-TSG), a stilbene glycoside, has hepatoprotective and/or hepatotoxic effects in a liver injury model. Methods: C57BL/6J mice were administered α-naphthylisothiocyanate (ANIT) to induce cholestasis, followed by treatment with cis-TSG. Hepatoprotective and hepatotoxic effects were assessed using serum biomarkers, liver histology, and metabolomic and lipidomic profiling. Transcriptomic analysis were conducted to explore gene expression changes associated with lipid and bile acid metabolism, inflammation, and oxidative stress. Results and Discussion: ANIT administration caused significant liver injury, evident from elevated alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels and dysregulated lipid metabolism. cis-TSG treatment markedly reduced ALT and AST levels, normalized lipid profiles, and ameliorated liver damage, as seen histologically. Metabolomic and lipidomic analyses revealed that cis-TSG influenced key pathways, notably glycerophospholipid metabolism, sphingolipid metabolism, and bile acid biosynthesis. The treatment with cis-TSG increased monounsaturated and polyunsaturated fatty acids (MUFAs and PUFAs), enhancing peroxisome proliferator-activated receptor alpha (PPARα) activity. Transcriptomic data confirmed these findings, showing the downregulation of genes linked to lipid metabolism, inflammation, and oxidative stress in the cis-TSG-treated group. The findings suggest that cis-TSG has a hepatoprotective effect through modulation of lipid metabolism and PPARα activation.